Pengaruh Permainan Ice Breaking (Estafet Kertas) sebagai Media Terapi Bermain Motorik Kasar di SDN 3 Sukajadi - Tarsim Putri, Suci Ambarwati; Sari, Deuis Diana; Ismawati, Alvira; Tiara Ningrum, Putri Azizah; Wiji Safitri, Desti Riyasti; Aryanti, Ayu Sri; Wardana, Mahadiaz Syah; Firmansyah, Andan (Kolaborasi: Jurnal Pengabdian Masyarakat, 2024)
Introduction: In children aged 6-13 years, children's fine motor movement settings vary and develop optimally, but some children still experience difficulties in coordinating their eyes and hands. and stimulation is needed to improve coordination of fine motor movements so that children are able to regulate eye and hand, arm and body movements simultaneously. Objective : This health education and game aims to improve PHBS behavior and improve gross motor skills for students at SDN 3 Sukajadi so they understand and know about the game method. Method: The counseling was carried out at one of the schools in Ciamis Regency, namely SDN 3 Sukajadi, which was the main target of this outreach. Partners in this health consultation are 34 students. The method used was a quantitative method, seminars and interviews which began with conducting a survey to determine the level of students' knowledge about the importance of PHBS behavior and also the ice breaking relay game. Then prepare the material to be presented in the form of pictures and leaflets, prepare a questionnaire for students to complete. Result: The results of the counseling survey involved 34 participants using interviews in the pre-test and questionnaires in the post-test. Researchers analyzed the completed questionnaires to determine the level of students' knowledge about the paper relay ice breaking game before and after health education activities. Conclusion: Health education can educate students to improve children's abilities regarding the paper ice breaking relay game both from a physical and motoric perspective.